2021
DOI: 10.1038/s41598-021-88273-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors affect the susceptibility to bacterial infections in diabetes

Abstract: Diabetes increases the risk of bacterial infections. We investigated whether common genetic variants associate with infection susceptibility in Finnish diabetic individuals. We performed genome-wide association studies and pathway analysis for bacterial infection frequency in Finnish adult diabetic individuals (FinnDiane Study; N = 5092, Diabetes Registry Vaasa; N = 4247) using national register data on antibiotic prescription purchases. Replication analyses were performed in a Swedish diabetic population (AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies have shown that impaired immunity in the hyperglycemic environment can lead to an increased incidence and severity of bacterial infections. 48 , 49 Chronic complications of diabetes, such as neuropathy, peripheral vascular disease, and increased expression of proinflammatory cytokines, have also been linked to microbial infection-related ulcerations in the skin and corneas. 50 In this study, we aimed to compare the impact of T1 and T2 DM on PCD pathways in response to Pa infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that impaired immunity in the hyperglycemic environment can lead to an increased incidence and severity of bacterial infections. 48 , 49 Chronic complications of diabetes, such as neuropathy, peripheral vascular disease, and increased expression of proinflammatory cytokines, have also been linked to microbial infection-related ulcerations in the skin and corneas. 50 In this study, we aimed to compare the impact of T1 and T2 DM on PCD pathways in response to Pa infection.…”
Section: Discussionmentioning
confidence: 99%
“…A SNP located most proximally to RELL1 was one of two SNPs to be most associated with persistent and intermittent nasal carriage of S. aureus in one population [93]. Finally, diabetes increases the risk of bacterial infections, and GWAS analysis for missense mutations identified RELL1 as one of two genes most likely mutated in a population of diabetic patients that purchased antibiotics [94], implicating RELL1 as being associated with both diabetes and bacterial infections.…”
Section: Regulation Of Bacterial Infectionmentioning
confidence: 96%